2012
DOI: 10.1038/mi.2011.40
|View full text |Cite
|
Sign up to set email alerts
|

Altered distribution of mucosal NK cells during HIV infection

Abstract: The human gut mucosa is a major site of HIV infection and infection-associated pathogenesis. Increasing evidence shows that natural killer (NK) cells play an important role in control of HIV infection but the mechanism(s) by which they mediate antiviral activity in the gut is unclear. Here we show two distinct subsets of NK cells exist in the gut, one localized to intraepithelial spaces (IEL) and the other to the lamina propria (LP). The frequency of both subsets of NK cells was reduced in chronic infection, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
59
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 46 publications
5
59
1
Order By: Relevance
“…Over the past decade, the importance of NK cells in controlling human immunodeficiency virus type 1 (HIV-1) infection in vivo has become increasingly clearer (1)(2)(3). In response, novel approaches to induce NK cell-directed enhancement of immune function are being developed (4).…”
mentioning
confidence: 99%
“…Over the past decade, the importance of NK cells in controlling human immunodeficiency virus type 1 (HIV-1) infection in vivo has become increasingly clearer (1)(2)(3). In response, novel approaches to induce NK cell-directed enhancement of immune function are being developed (4).…”
mentioning
confidence: 99%
“…Combinations of KIR and HLA alleles have been associated with HIV disease outcome, with enhanced NK cell function delaying AIDS progression (reviewed by [71]). A recent study has observed the presence of two distinct NK cell subsets residing in the gut with altered frequencies during HIV-infection [72]. Using immunochemistry of gut biopsies, Sip et al [72] demonstrated that intraepithelial and lamina propria NK cells express two different isoforms of Nkp46, a natural cytotoxicity receptor expressed on all NK cells.…”
Section: The Gastro-intestinal Lymphoid Tissue (Galt)mentioning
confidence: 99%
“…A recent study has observed the presence of two distinct NK cell subsets residing in the gut with altered frequencies during HIV-infection [72]. Using immunochemistry of gut biopsies, Sip et al [72] demonstrated that intraepithelial and lamina propria NK cells express two different isoforms of Nkp46, a natural cytotoxicity receptor expressed on all NK cells. In addition to harbouring a more terminally differentiated phenotype (CD57 + ), intraepithelial NK subset were observed more frequently among individuals with the protective KIR/HLA genotype associated with spontaneous control of HIV replication, implying a potential implication for intraepithelial NK in the control of viremia.…”
Section: The Gastro-intestinal Lymphoid Tissue (Galt)mentioning
confidence: 99%
See 1 more Smart Citation
“…[85][86][87][88] FccRIIIa is mostly expressed on NK cells and neutrophils, but other cell types such as macrophages, and eosinophils also express this receptor at low levels. 89,90 As NK cells are mostly present in the circulatory system, they may play a critical role in killing recently reactivated CD4 T cells in the blood, while tissue-specific killing may rely on other mechanisms. Several neutralizing and non-neutralizing HIV-specific mAbs have been tested in various ADCC assays.…”
Section: Antibody-dependent Cellular Cytotoxicity (Adcc)mentioning
confidence: 99%